Plasticidade fenotípica da morfologia externa de Lippia alba (Mill.) N. E. Br. ex Britt. & Wilson (Verbenaceae) em resposta a níveis de luminosidade e adubação - Montanari, R. M.; Sousa, L. A. [UNESP]; Leite, M. N.; Coelho, A. D F; Viccini, L. F.; Stefanini, M. B. [UNESP] (My University, 2004)
The objective of this paper was to evaluate the phenotypical plasticity of external morphology of Lippia alba in response to two luminosity level and four organic-mineral fertilization level. The morphological plasticity was quantified by the phenotypic variation intensity of the morphological characters (ramifications, leafs, inflorescences, flowers, height, stem diameter, leaf blade length, foliar blade breadth and space between branches). It was possible to verify significant effect as a consequence of luminosity and substratum variations. However, the interaction between these factors was not observed suggesting that they act independently. The majority of characters revealed high magnitude of phenotypical plasticity. The results obtained suggest that luminosity intensity and substratum quality contribute to amplify the phenotypical expression of Lippia alba.
Phenotypical plasticity of the external morphology in Lippia alba (Mill.) N. E. Br. ex Britt & Wilson in response to level of luminosity and fertilization
Keywords: External morphology; Fertilization; Lippia alba; Luminosity; Phenotypical plasticity; mineral; fertilizer application; flower; foliar blade breadth; inflorescence; light intensity; Lippia; luminance; morphological trait; nonhuman; phenotypic plasticity; phenotypic variation; plant height; plant leaf; plant morphology; plant stem; soil; stem diameter; substratum